2015
DOI: 10.2217/imt.14.98
|View full text |Cite
|
Sign up to set email alerts
|

Adoptive Cell Therapy for Sarcoma

Abstract: Current therapy for sarcomas, though effective in treating local disease, is often ineffective for patients with recurrent or metastatic disease. To improve outcomes, novel approaches are needed and cell therapy has the potential to meet this need since it does not rely on the cytotoxic mechanisms of conventional therapies. The recent successes of T-cell therapies for hematological malignancies have led to renewed interest in exploring cell therapies for solid tumors such as sarcomas. In this review, we will d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 152 publications
0
9
0
Order By: Relevance
“…An alternative approach to alteration of the tumor microenvironment is the introduction of autologous T-cells with enhanced activity against a specific tumor epitope. Instead of systemic modification of the immune system with a receptor antibody such as an anti-PD1, this approach allows direct introduction of a confirmed tumor antigen in an effort to activate the immune system against the neoplasm (64). Currently two main technologies of adoptive T cell immunotherapies are being utilized; in one method chimeric antibody receptor engineered T cell (CAR-T) which focuses on helping the immune cells recognize the tumor antigens and then directing them to locate and kill the target tumor cells.…”
Section: T-cell Targeted Approachmentioning
confidence: 99%
“…An alternative approach to alteration of the tumor microenvironment is the introduction of autologous T-cells with enhanced activity against a specific tumor epitope. Instead of systemic modification of the immune system with a receptor antibody such as an anti-PD1, this approach allows direct introduction of a confirmed tumor antigen in an effort to activate the immune system against the neoplasm (64). Currently two main technologies of adoptive T cell immunotherapies are being utilized; in one method chimeric antibody receptor engineered T cell (CAR-T) which focuses on helping the immune cells recognize the tumor antigens and then directing them to locate and kill the target tumor cells.…”
Section: T-cell Targeted Approachmentioning
confidence: 99%
“…It was demonstrated that a marked increase in IFN-γ, GM-CSF, TNF-α, IL-6, and IL-10 occurred shortly after the lymphocyte infusion ( 108 ). Incorporation of suicide genes or engineering of multi-specific CAR-T cells to limit their activation to tumor sites might allow control of adverse events ( 109 ). In summary, adoptive transfer of CAR-T cells appears to be an attractive therapeutic option for experimental osteosarcoma therapy, but further research will be required to develop comprehensive measures to avoid adverse side effects.…”
Section: Adoptive T Cell Transfer For Osteosarcomamentioning
confidence: 99%
“…Cytokines mediate various activities of the cells involved in innate immunity. T and B Various subtypes of sarcomas express TAAs that allow the development of cellular immunotherapies [20]. In particular, some sarcomas have specific chromosomal translocations that may serve as unique targets for immunotherapy [21].…”
Section: Target Of Cellular Immunotherapymentioning
confidence: 99%